Characterization of pTS14, an IncF2:A1:B1 Plasmid Carrying tet(M) in a Salmonella enterica Isolate - Liu, Ying-ying; Liu, Xiao-kang; Cui, Xiao-die; Chen, Min; Li, Shuai-hua; He, Dan-dan; Liu, Jian-hua; Yuan, Li; Hu, Gong-zheng; Pan, Yu-shan (Frontiers in Microbiology, 2020)
The objective of this study was to explore the genetic and biological features of the tet(M)-harboring plasmid pTS14 in Salmonella enterica strain S14 isolated from a chicken fecal sample. Plasmid pTS14 was identified by conjugation, S1-pulsed-field gel electrophoresis, Southern hybridization, and plasmid sequencing. The biological characteristics of pTS14 were assessed via stability, growth kinetics, and starvation survival experiments. Strain S14, belonging to ST3007, harbored a 119-kb tet(M)-bearing IncF2:A1:B1 conjugative plasmid pTS14. The plasmid pTS14 contained a novel transposon Tn6709 with the genetic structure IS26-tnpA1-tnpA2-∆orf13-LP-tet(M)-tnpX-∆tnpR-IS26, and the resistance genes tet(B), tet(D), strAB, sul2, and blaTEM-1b. In addition, pTS14 was found to be highly stable in the recipient strain E. coli J53. The transconjugant TS14 exhibited a higher survival ratio than E. coli J53 under permanent starvation-induced stress. The tet(M)-bearing IncF2 epidemic plasmid lineage may accelerate the dissemination of tet(M) and other genes by coselection, which could constitute a potentially serious threat to clinical treatment regimens.